2013
DOI: 10.1890/es13-00120.1
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Kok effect to light: A review on the integration of daytime respiration and net ecosystem exchange

Abstract: Net ecosystem exchange (NEE) represents the difference between carbon assimilated through photosynthesis, or gross primary productivity (GPP), and carbon released via ecosystem respiration (ER). NEE, measured via eddy covariance and chamber techniques, must be partitioned into these fluxes to accurately describe and understand the carbon dynamics of an ecosystem. GPP and daytime ER may be significantly overestimated if the light inhibition of foliar mitochondrial respiration, or “Kok effect,” is not accurately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
155
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(165 citation statements)
references
References 114 publications
(176 reference statements)
8
155
2
Order By: Relevance
“…We found that, at 21% O 2 , respiration was light-inhibited (based on the non-linearity in the 335 light response curve of A net ), as has been commonly found in other experiments (Atkin et al 336 2005;Tcherkez et al 2008;Heskel et al 2013). However, at 2% O 2 , light did not inhibit 337 mitochondrial respiration (i.e.…”
Section: Mitochondrial Respiration In the Light 334supporting
confidence: 73%
“…We found that, at 21% O 2 , respiration was light-inhibited (based on the non-linearity in the 335 light response curve of A net ), as has been commonly found in other experiments (Atkin et al 336 2005;Tcherkez et al 2008;Heskel et al 2013). However, at 2% O 2 , light did not inhibit 337 mitochondrial respiration (i.e.…”
Section: Mitochondrial Respiration In the Light 334supporting
confidence: 73%
“…1). Nearcomplete inhibition of leaf respiration by light has been reported for individual leaves of some species 10 , and so both the seasonal pattern and the magnitude of the discrepancy between daytime and night-time ecosystem respiration are consistent with a plausible ecosystem-scale Kok effect.…”
supporting
confidence: 65%
“…As belowground respiration typically varies by less than 10% between daytime and night-time at this site 20 , the large discrepancy between daytime and night-time ecosystem respiration in the first half of the growing season suggests inhibition of leaf respiration by light, known as the Kok effect 9 . Such inhibition has been found to occur at the leaf level in many plant species 10 , including tree species 11 (although we know of no published studies in red oak, which dominates our site). We therefore asked: what would cause inhibition of leaf respiration to occur during the first half of the growing season only, and is the magnitude of the discrepancy consistent with the overall respiration budget?…”
mentioning
confidence: 86%
“…R day is as yet not well understood in terms of responses to environmental variation or temperature dependence and hence is difficult to model (Tcherkez et al, 2012;Heskel et al, 2013;Way & Yamori, 2014). It is widely understood that estimates of R day obtained from A-C i curves are inaccurate.…”
Section: Researchmentioning
confidence: 99%